European Union Foreign Policy towards Jordan - Abu Hmeidan, Rima; Hamendi, Nadia (Opción)
This study aims to analyze and explain the attitudes and orientations of the European Union’s foreign policy towards Jordan. Moreover, it aims to show that Jordan’s role and strong influence in the regional, security and humanitarian levels impacts the EU’s foreign policy towards Jordan which works, within a framework of partnership, towards enhancing and strengthening the EU’s political and economic relations with Jordan. No less important than the security interest, the economic dimension also constitutes a core axis in the relations between the two sides, where European economic support is a main determinant in the relations between the two sides. The study concludes that the Partnership Agreement between the EU and Jordan aimed to establish a proper framework for political dialogue that allows for the development of political, economic, monetary and social relations, ensuring regional stability, especially in the fight against terrorism and extremism, in addition to encouraging regional cooperation to bring about a closer understanding of political stances on international affairs by enabling each side to understand and appreciate the other’s position